Comparative Analysis of Traditional vs Online Learning in Second Language Acquisition: The Case of Uzbekistan - Zakirova. Sh. I; Rasulova. S. D (Development in Language Studies, 2025)
Second language acquisition (SLA) in Uzbekistan has undergone significant transformation with the integration of digital technologies into education. This study compares traditional face-to-face learning and online learning methods in SLA, specifically analyzing their effectiveness, advantages, and challenges within the Uzbek educational context. The research reviews key linguistic theories, examines empirical studies conducted in Uzbekistan, and evaluates factors such as student engagement, retention, and interaction in both modalities. Findings indicate that while traditional learning in Uzbek schools and universities provides structured and immersive language experiences, online learning offers flexibility and access to diverse digital tools, especially in remote regions where traditional classroom resources may be limited. The study concludes with recommendations for hybrid learning models that combine the strengths of both approaches, ensuring effective and inclusive language education in Uzbekistan.